CHALLENGING PATRIARCHY: LIBERAL FEMINISM IN MULAN (2020) - Hasibuan, Debby Melviana; Purwarno, Purwarno (JOURNAL OF LANGUAGE, 2025)
This study examines gender equality through the lens of liberal feminism in the film Mulan (2020), addressing a significant research gap in existing feminist analyses of the film. While previous studies have examined Mulan's character from various perspectives, this research focuses specifically on how her character development and actions reflect liberal feminist principles, offering a fresh perspective on her challenge to patriarchal norms. Data was collected and analyzed using qualitative textual analysis, which involves a close examination of key dialogues, character interactions, and narrative choices within the film. This method allows for a deeper understanding of how Mulan's journey embodies the ideals of liberal feminism, particularly in its defiance of traditional gender roles and its advocacy of individual agency. This study argues that the character of Mulan represents a meaningful redefinition of female agency through liberal feminist ideals. By portraying a strong female protagonist who challenges societal expectations, the film reinforces feminist discourse and highlights the evolving representation of female empowerment in contemporary cinema.